Quick Assesment Study On Condition Of Marine Debris From Fisheries Activities At Tegalsari Fishing Port In Tegal City - Nugroho, Beni Sabdo; Listyanto, Ilham Bayu Anggita; Simanjuntak, Susi Watina; Zuhry, Noor; Kusnandar, Kusnandar; Alamsyah, Heru Kurniawan; Mulyani, Sri (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
Waste is a significant environmental issue faced by one of the largest fishing ports in Central Java, PPP Tegalsari. PPP Tegalsari has been reported to have a slum status, evidenced by the accumulation of trash at key points in the port. The purpose of this rapid assessment activity is to evaluate the waste management status and waste conditions in the Tegalsari Coastal Fishing Port area. Primary data was collected through observations, in-depth interviews using an interview guide, and surveys using questionnaires and waste calculation forms, while secondary data was gathered from government stakeholders, scientific journals, and reports from relevant agencies. The results of the Rapid Assessment conducted from June 14, 2021, to June 19, 2021, include infrastructure facilities for waste management, human resources, waste management policies, sources of waste activities, daily waste generation, potential leakage of waste into the sea, waste composition, and waste management in the area, indicating that approximately 2,240 kg/day of waste is generated at the Tegalsari Fishery Port during times of low ship activity, with the fish processing/filleting industry producing the most waste at 652.3 kg/day, while the dock area generates the least amount at 287 kg/day. The handling of plastic waste management on the fishing vessel PPP Tegalsari consists of two methods: direct disposal into the sea and return to the port. The implementation of waste management based on handling and reducing waste is still in its early stages due to the fact that several requirements have not yet been met. It can be concluded that the waste conditions and waste management at PPP Tegalsari require improvements in waste management infrastructure, capacity building, the establishment of waste management institutions, as well as regulatory improvements and the creation of a sustainable waste management system.